The Dual Angiogenesis Effects via Nrf2/HO-1 Signaling Pathway of Melatonin Nanocomposite Scaffold on Promoting Diabetic Bone Defect Repair - Chen T; Wu Z; Hou Q; Mei Y; Yang K; Xu J; Wang L (International Journal of Nanomedicine, 2024)
Tingting Chen,1 Zimei Wu,1,2 Qiaodan Hou,1 Yixin Mei,1 Kunkun Yang,1 Jing Xu,3 Lin Wang1,3 1School of Medicine, Southern University of Science and Technology, Shenzhen, People’s Republic of China; 2Department of Orthopedic Surgery, The Seventh Affiliated Hospital, Sun Yat-Sen University, Shenzhen, People’s Republic of China; 3Southern University of Science and Technology Hospital, Shenzhen, People’s Republic of ChinaCorrespondence: Lin Wang, Email wangl7@sustech.edu.cnPurpose: Given the escalating prevalence of diabetes, the demand for specific bone graft materials is increasing, owing to the greater tendency towards bone defects and more difficult defect repair resulting from diabetic bone disease (DBD). Melatonin (MT), which is known for its potent antioxidant properties, has been shown to stimulate both osteogenesis and angiogenesis.Methods: MT was formulated into MT@PLGA nanoparticles (NPs), mixed with sodium alginate (SA) hydrogel, and contained within a 3D printing polycaprolactone/β-Tricalcium phosphate (PCL/β-TCP) scaffold. The osteogenic capacity of the MT nanocomposite scaffold under diabetic conditions was demonstrated via in vitro and in vivo studies and the underlying mechanisms were investigated.Results: Physicochemical characterization experiments confirmed the successful fabrication of the MT nanocomposite scaffold, which can achieve long-lasting sustained release of MT. The in vitro and in vivo studies demonstrated that the MT nanocomposite scaffold exhibited enhanced osteogenic capacity, which was elucidated by the dual angiogenesis effects activated through the NF-E2–related factor 2/Heme oxygenase 1 (Nrf2/HO-1) signaling pathway, including the enhancement of antioxidant enzyme activity to reduce the oxidative stress damage of vascular endothelial cells (VECs) and directly stimulating vascular endothelial growth factor (VEGF) production, which reversed the angiogenesis-osteogenesis uncoupling and promoted osteogenesis under diabetic conditions.Conclusion: This study demonstrated the research prospective and clinical implications of the MT nanocomposite scaffold as a novel bone graft for treating bone defect and enhancing bone fusion in diabetic individuals. Keywords: diabetic bone defect, melatonin, Nrf2/HO-1 signaling pathway, dual angiogenesis effects, 3D printing